A review on application of Holland’s RIASEC theory in educational settings - Zainudin, Zaida Nor; Foon, Lai Wei; Mohamad Yusop, Yusni; Wan Othman, Wan Norhayati; Engku Kamarudin, Engku Mardiah; Anuar, Muharram (Human Resource Management Academic Research Society, 2024)
RIASEC typological theory of persons and environments is regarded as one of the most influential theory in the field of career counseling. This theory is extensively used as a holistic career theory attending to the needs of students on career choices, that subsequently influence their college majors. Some empirical literatures show shortcomings of RIASEC while others indicated it is still the simplest measure to be used in school, college or university settings for quick understanding. Some findings also highlighted that RIASEC’s interest definition maybe at its best with combination of other additional interest measures. Hence, the purpose of this study was to identify how Holland’s RIASEC theory was used in students from various educational settings. The methodology applied inclusion and exclusion criteria based on the SCOPUS, Wiley, Ebscohost and Google Scholar database. The results of this review address that RIASEC play a significant role in career decision-making and academic achievements, with considerations for individual differences by sex and the influence of additional dimensions such as personality traits and abilities and also clarify the gaps and limitations in the body of research evaluating the application of Holland’s RIASEC theory in educational setting in various nations. Through the process, ten articles in total were chosen. The results of this review are helpful for counselors and other professionals in the mental health field who work with families and students. Counsellors can use this information to help them create counseling plans for their clients that take into account the significance of raising parents' and students' awareness of the importance of choosing majors that complement each student's personality.